Interactions between Pied crows Corvus albus and breeding White-backed vultures Gyps africanus. Issue 3 (4th May 2019) - Johnson, Thomas F.; Murn, Campbell
Abstract : African White-backed vultures Gyps africanus are Critically Endangered, mainly due to mortality from poisoning, but the species also exhibits variable breeding productivity that may partially be explained by nest failure due to predation. Pied crows Corvus albus have been implicated as nest predators, but because there is no evidence linking Pied crows to low breeding productivity of White-backed vultures, we used a combination of dummy eggs (n = 14) and camera traps on active nests (n = 10), to investigate what species visit White-backed vulture nests (both active and abandoned) and predate on their eggs. We recorded 47 egg predation events, of which 37 (79%) were attributable to Pied crows, while other predators (unidentified large raptors, White-backed vultures and Vervet monkeys) were recorded interacting with eggs 5 times in total; mobbing by Pied crows of incubating vultures increased the probability vultures would abandon their nest but crows did not eat abandoned eggs as soon as they were available. Further studies are needed across a wider range of vulture breeding areas to contextualise these findings both in terms of breeding productivity and the significant risks of mortality faced by vultures from poisoning and other threats.